PENGARUH KOREAN WAVE, PARASOCIAL RELATIONSHIP, DAN BRAND AMBASSADOR TERHADAP BRAND LOYALTY - Ningsih, Masyitoh Febriatin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Hallyu or commonly known as the Korean wave includes Korean traditional culture which is then combined with various fields, such as in music there is K-Pop, in the field of food K-Food, in the field of fashion known as K-Style, and also in the field of film or drama better known as K-Movie or K-Drama. K-Pop fans are said to be loyal fans because of the parasocial relationship that occurs between fans and idol characters. Therefore, fans will enthusiastically buy or use products advertised by idol characters. This study aims to identify the effect of Korean wave, parasocial relationship, and brand ambassador on the loyalty of Shopee users in Malang. This is explanatory research, which explains the relationships between variables being studied. The data of this research was harvested from online questionnaires through Google Forms, distributed to 100 Shopee users in Malang as the sample. Here multiple linear regression analysis was conducted in IBM SPSS 28.0. this study finds that Korean wave does not significantly influence the brand loyalty of Shopee users in Malang city, that parasocial relationship does not significantly affects the brand loyalty of Shopee users in Malang city, and that brand ambassador positively and significantly influences the brand loyalty of Shopee users in Malang city.